Edukasi Audio-Visual Latihan Baduanjin terhadap Pengetahuan Tanda Peringatan Strok pada Kelompok Risiko Strok - Putri, Tri Antika Rizki Kusuma; Supriatin, Eva; Hayati, Suci Noor; Pratiwi, Gilang Dwi; Puspasari, Susy (Universitas Faletehan, 2023)
Baduanjin exercise has an influence on cardiovascular system and stress which often occurs in stroke risk group. However, the pandemic condition limited nurses to provide education to them. Thus, the audio-visual educational media of Baduanjin exercise was created as an alternative for providing remote education. This study aimed to examine the effectiveness of audio-visual educational media on the knowledge of stroke warning signs in stroke risk group. This research used a quasi-experimental approach and a one group pre-posttest design involving 47 respondents. The stroke risk group was identified based on stroke risk factors, followed by pre-test measurements. The used instrument contained of 12 items of stroke symptoms. The paired t-test was used to measure differences in knowledge scores of stroke risk group. The respondents received a link to educational materials that can be accessed anywhere without the need for face-to-face contact. The pre and posttest scores were analyzed using paired t-test and showed that there was a significant difference in the mean of knowledge of the stroke risk group before and after getting Baduanjin exercise audio-visual educational media (p value<0.000). Audio-visual educational media had a significant influence on the knowledge scores of the stroke risk group. The method of providing virtual education can be an alternative for nurses during the pandemic so that nurses can still carry out their role as educators.